Myeloid-Derived Suppressor Cells and γδT17 Cells Contribute to the Development of Gastric MALT Lymphoma in H. felis-Infected Mice - Zhao, Yanan; Lu, Fei; Ye, Jingjing; Ji, Min; Pang, Yihua; Wang, Yan; Wang, Lingbo; Li, Guosheng; Sun, Tao; Li, Jingxin; Ma, Daoxin; Ji, Chunyan (Frontiers in Immunology, 2020)
In gastric MALT lymphoma, Helicobacter pylori (HP)-induced chronic inflammation and immune disorders are closely associated with the development of tumor. Myeloid‑derived suppressor cells (MDSCs), recognized as a strong immunosuppressive cell population, have been proved to exert pivotal functions in promoting numerous solid tumor. Yet the precise mechanism of MDSCs activation is still unclear. In this study, we use Helicobacter felis (H.felis)-infected mice as murine models to study gastric MALT lymphoma development, and dynamically monitor gastric pathological characteristics as well as immune homeostasis imbalance post-infection. Our studies indicate an infiltration and enrichment of MDSCs in MALT lymphoma patients. Moreover, Arg-1, iNOS, as well as relative cytokines IL-23 and IL-1β were significantly increased in gastric MALT lymphoma tissue. Accordingly, we validated in H.felis-infected murine model an overexpression of MDSCs (Gr-1+CD11b+), γδT17, relative cytokines and molecules. These findings shed light on functions and mechanisms of MDSCs and γδT17 in immune dysregulation of gastric MALT lymphoma development and provide novel therapeutic targets for gastric MALT lymphoma.